Preprocedural but not periprocedural high‐sensitive Troponin T levels predict outcome in patients undergoing transcatheter aortic valve implantation. Issue 6 (December 2016) - Köhler, Wiebke M.; Freitag‐Wolf, Sandra; Lambers, Moritz; Lutz, Matthias; Niemann, Philip Maximilian; Petzina, Rainer; Lutter, Georg; Bramlage, Peter; Frey, Norbert; Frank, Derk
Summary: Aim: Risk assessment of patients undergoing transcatheter aortic valve implantation (TAVI) remains difficult. Biomarkers have been shown to provide potential prognostic information. Here, we aimed to analyze whether the biomarker high‐sensitivity Troponin T (hsTNT) could be used to improve risk stratification. Method: We prospectively enrolled 267 patients undergoing TAVI. Biomarkers (hsTNT and NTproBNP) were measured 1 day before, and 3 and 7 days postprocedure. All possible prognostic factors upon survival time were analyzed by Cox regression analysis. Results: A total of 259 patients (mean age 82±6.1 years) were available for complete follow‐up. The median Logistic EuroSCORE (Log ES) and Log ES II were 21.16% (Q1=13.92; Q3=34.27) and 6.42% (Q1=3.89; Q3=11.07), respectively. Median follow‐up was 290 (Q1=88; Q3=529) days. A total of 71 deaths occurred during follow‐up, and the 30‐day mortality was 5.8%. Median baseline hsTNT was 27.4 pg/mL (Q1=16.2; Q3=46 pg/mL). From all potential mortality‐associated factors, only preprocedural hsTNT level ( P =.001), elevated Log ES ( P =.03) as well as acute kidney injury ( P <.001) and chronic obstructive pulmonary disease (COPD) ( P =.039) emerged as independent prognostic parameters for adverse outcome. We also tested whether the Valve Academic Research Consortium‐2 (VARC‐II) cutoff for myocardial damage (hsTNT peak value exceeding 15× the upper reference limit + at least 50% increase) was of prognostic relevance. At 72‐hours post‐TAVI, 36.2% of the patients matched these VARC‐II criteria of myocardial damage. However, these patients did not display a difference in survival compared to patients without significant myocardial injury. Conclusion: Elevated preprocedural hsTNT represents an independent risk predictor of all‐cause death while periprocedural hsTNT elevation failed to show prognostic relevance.